2020
DOI: 10.3390/ani10091511
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Detection in Veterinary Species: Investigation of Commercial ELISA Kits

Abstract: In human medicine, procalcitonin (PCT), the precursor of calcitonin, is used for the rapid identification of the origin and severity of sepsis. In veterinary medicine, PCT has been studied in horses, cattle, and dogs, but the use of PCT in diagnostic and/or prognostic settings is not possible because of the lack of validated assays to obtain reference ranges. The aim of the present study was the investigation of commercially available ELISA kits for the detection of canine and equine PCT in plasma samples. Val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…PCT has also similarly been used in conjunction with other clinicopathologic results as an indicator of intestinal ischaemia to identify horses with a strangulating lesion, necessitating surgery (Kilcoyne et al 2020). Recently, a human PCT ELISA kit was found to be suitable to detect equine PCT with a limit of detection of 56 ng/mL (Battaglia et al 2020). In foals, however, PCT was not a useful biomarker in pneumonia associated with Rhodococcus equi (Barton et al 2016) and there was no significant difference in leukocyte PCT mRNA levels identified between septic and nonseptic foals (Pusterla et al 2006).…”
Section: Duration Of Antimicrobial Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…PCT has also similarly been used in conjunction with other clinicopathologic results as an indicator of intestinal ischaemia to identify horses with a strangulating lesion, necessitating surgery (Kilcoyne et al 2020). Recently, a human PCT ELISA kit was found to be suitable to detect equine PCT with a limit of detection of 56 ng/mL (Battaglia et al 2020). In foals, however, PCT was not a useful biomarker in pneumonia associated with Rhodococcus equi (Barton et al 2016) and there was no significant difference in leukocyte PCT mRNA levels identified between septic and nonseptic foals (Pusterla et al 2006).…”
Section: Duration Of Antimicrobial Administrationmentioning
confidence: 99%
“…Recently, a human PCT ELISA kit was found to be suitable to detect equine PCT with a limit of detection of 56 ng/mL (Battaglia et al . 2020). In foals, however, PCT was not a useful biomarker in pneumonia associated with Rhodococcus equi (Barton et al .…”
Section: Duration Of Antimicrobial Administrationmentioning
confidence: 99%
“…This is of particular interest for ePCT, due to the current lack of specific anti-equine antibodies. In fact, available ELISA kits for ePCT (for research purposes only) are based on human anti-PCT antibodies [17,20] thanks to the homology between equine and human PCTs [39]. Nevertheless, the limit of detection obtained in these studies is higher than that reported by manufacturer's instructions of equine PCT kit and this could be related to the use of non-species specific i.e.…”
Section: Selectivity Of the Pne-based Mipsmentioning
confidence: 85%
“…Conversely, in veterinary patients, only three commercial ELISA kits are available for dogs or horses, not fully validated, and suitable only for research purposes. In particular, only one ELISA-type immunoassay is reported in literature for equine PCT, based on human antibodies since there is no availability of specific antibodies [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, enzyme-linked immunosorbent assay is the most widely used method for the detection of ricin [9][10][11]. Corresponding commercial detection kits have also been developed, but the sensitivity and detection range are limited [12][13][14]. In order to improve the detection sensitivity, our laboratory also tried to amplify the detection signal with isothermal ampli cation, and the detection sensitivity was improved to a certain extent [15].…”
Section: Introductionmentioning
confidence: 99%